The relationship between chronotype and personality among patients with alcohol dependence syndrome: Pilot study. (25th November 2016) - Nowakowska-Domagała, Katarzyna; Mokros, Łukasz; Jabłkowska-Górecka, Karolina; Grzelińska, Joanna; Pietras, Tadeusz
ABSTRACT: The study investigates the distribution of chronotypes among alcohol-dependent subjects and the relationship between personality and chronotype. Fifty-eight alcohol-dependent patients and 29 age-matched healthy controls were studied using Ogińska's Chronotype Questionnaire (ChQ), Eysenck's Personality Questionnaire – Revised (EPQ-R), Selzer's Michigan Alcoholism Screening Test (MAST) and a sociodemographic status questionnaire designed by the authors. The alcohol-dependent patients tended to be morning type, based on the morningness–eveningness ChQ scale, with a weakly marked rhythm, based on the distinctness ChQ scale. Preference towards morningness was associated with older age, but no relation between chronotype and severity of alcohol dependence was found. A high amplitude of the rhythm was associated with higher neuroticism. Therefore, despite being in the minority, patients with a distinct circadian rhythm (i.e. with a high amplitude) are at greater risk of mood and anxiety disorders and hence should be given special consideration.